A new species of Tillandsia (Bromeliaceae) from the Cañón de Escahuasco, Puebla, Mexico - Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Ceja-Romero, Jacqueline; Mendoza-Ruiz, Aniceto (Instituto de Ecología, A.C., 2011)
Tillandsia escahuascensis, a saxicolous species from the Cañón de Escahuasco, municipio de Tetela de Ocampo, Puebla, Mexico, is described and illustrated. The new taxon shares some similarities with T. parryi and T. suesilliae, but it is easily distinguished by its 2-3 branched inflorescences with very narrowly oblong to linear and long stipitate spikes.